Numerical Evaluation of Transversal Strength of Traditional Fishing Vessel in Penajam Paser Utara, East Kalimantan, Indonesia - Pawara, Muhammad Uswah; Alamsyah; Arifuddin, Andi Mursid Nugraha; Tobing, Andreyano Yosefan Lumban; Hidayat, Taufik; Nurcholik, Samsu Dlukha; Syadzali, Abdul Mujib (Naval Architecture Department, Kalimantan Institut of Technology, 2023)
Challenges in procuring wood as the primary material for ships have led to a decline in overall quality. Meeting the demands of shipbuilding often involves neglecting consideration for the quality and characteristics of construction materials. Additionally, the shipbuilding process commonly overlooks technical and operational aspects associated with construction specifications. Ship damages frequently result from the selection of wood types, sizes, and ages that do not meet construction criteria or fall below the standards for achieving optimal construction. Many ship constructions are identified that fail to meet the requirements for ensuring the safety and security of the crew, ship, and cargo during operations. This research aims to numerically assess the transverse strength of fishing vessels operating in Penajam Paser Utara using Ansys software. Survey results indicate an average size of fishing boats in this area as 10 – 20 meters in length. 2.6 - 3.5 meters in width, and 1.6 – 2.5 meters in height. The stress analysis results from Ansys Workbench were recorded at 2.3402 MPa